SISTEM INFORMASI RETRIBUSI PADA DINAS PERKIM DAN LH DI BIDANG PENGOLAHAN PEMBUANGAN SAMPAH KABUPATEN PEKALONGAN BERBASIS ANDROID - Aslam Fatkhudin (Curtina, 2021)
The Department of Settlement and Environment (Dinas Perkim and LH) of Pekalongan Regency is the agency responsible for managing cleanliness. Garbage in Pekalongan Regency is one of the problems that does not have a long-term solution. Several problems related to waste, such as the location of the Final Disposal Site which is already over capacity, the management of waste retribution is not optimal, and the community is less involved in waste management. This study discusses the system of retribution for garbage collection. The collection of retribution for waste services often does not run smoothly due to several problems, such as the lack of waste transporters, the distribution of transport areas that have not been maximized, the community's lack of discipline in paying the waste retribution, and the absence of a system that supports the management of integrated waste retribution payment information. In order for the waste retribution payment procedure to be orderly, the waste management department needs to build a waste retribution payment information system. Therefore, the author makes a retribution information system at the Pekalongan Regency Perkim and LH Office based on Android. This system aims to make it easier for people to pay waste fees and also make it easier for employees in the data collection process and report generation with the data stored properly.